Smart Expo UMKM Based on Extreme Programming Method: Evaluating on Black Box and UAT - Pratama, I Putu Agus Eka; Andreyana, Putu Veda; Putra, Yogiswara Dharma (Indonesian Scientific Journal, 2024)
The rapid development of information technology (IT) and the post-Covid-19 pandemic conditions provide joint learning to provide an online service that allows a business expo event to be carried out virtually and online based on the web. UMKM or Micro, small, and medium enterprises (MSMEs), as the spearhead of the people's and regional economies, can utilize IT to improve product marketing and distribution through web-based virtual expos. For this reason, this study carried out the design and implementation of a web-based smart virtual expo using the Extreme Programming development method in a case study of the MSME business expo event in X Regency. The Extreme Programming development method was chosen to facilitate the adjustment of user needs to the virtual expo website developed through active communication with users during the development process and to make development possible in a relatively short time. This study uses a qualitative case study research method and the Black Box Testing method on the developer side and User Acceptance Testing (UAT) on the user side. The results of the study on Black Box Testing showed that all functionalities on the developed Smart Virtual Expo prototype can run well, and all users can accept the prototype well, with the largest age range at 41-50 years (56.8%) can use the prototype to access information and videos of products.